Pecado e punição no cordel de metamorfose nordestino: resíduos de uma mentalidade medieval - Araújo, Camille Feitosa de (2016)
This study intends to analyze some popular narrative poems known in Brazil as “Cordeis de Metamorfose” in order to identify residues of medieval mentality regarding sin and punishment in the imagery portrayed by popular poets from northeast Brazil. The idea of sin was transmitted to us as a transgression of divine laws. In the Middle Ages, this conception was propagated by Catholic Church as a way of combating vices, almost always with regard to capital sins, and of disciplining the conduct of Christians. Although many centuries separate us from the Middle Ages, the Christian medieval mentality is still fairly entrenched in our culture. Therefore, in this work, we present an analysis of the notion of sin and its possible implications in the medieval context with the aim of demonstrating the residual presence of that matter in Cordel Literature, a kind of artistic popular manifestation. We show this presence from the research of those popular narrative poems that tell stories in which some characters transgress moral and/or religious principles and, for this reason, are transfigured into animals as punishment. Therefore, in the poems we analyzed, physical metamorphosis is considered a punishment, a mean of social exclusion that asserts the permanence of a medieval worldview. For a long time, this view distinguished and ignored minorities that were seen as individuals without good social practices. In order to understand how such mentality about sin and its consequences are present in the poetic work of the popular poets from northeast Brazil and, therefore, in the popular imagery, we make use of the Theory of Residuality. According to this theory, residues from the past and from an ancient culture remain in other cultures and in other times, which allow us to talk about residual heritage, in other words, there are cultural and mental sediments crystallized in the imagery portrayed by popular poets. Furthermore, we rely on studies of medievalists in order to understand better the Middle Ages, mainly the Late Middle Ages. Thus, popular literature is the starting point of a multidisciplinary and comparative study, as far as it interacts with other types of literary texts, as well as historiographic texts. It revisits important works of literature in the same way it reveals the mental subtract of the medieval social formations and of the residual culture of northeast Brazil that brings us to the imagery hybridized from the Middle Ages.